2006
DOI: 10.1029/2005gl025498
|View full text |Cite
|
Sign up to set email alerts
|

Circulation in the central equatorial Atlantic: Mean and intraseasonal to seasonal variability

Abstract: The zonal equatorial circulation of the upper 700 m in the central tropical Atlantic is studied based on 11 cross‐equatorial ship sections taken at 23–29°W during 1999 to 2005 and on data from a pair of moored Acoustic Doppler current profilers deployed on the equator at 23°W during February 2004 to May 2005. The observations on the equator reveal the existence of two mean westward cores of the Equatorial Intermediate Current below the Equatorial Undercurrent. In contrast to the 2002 moored observations at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
108
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(125 citation statements)
references
References 17 publications
16
108
1
Order By: Relevance
“…These results suggest that, while the EUC transport significantly decreases from 35°W to 26°W and loses about 6 Sv, it decreases only modestly farther east, losing 1.7 Sv between 26°W and 10°W. From the 12.1 Sv EUC total transport, 0.4 Sv occurs in the surface layer, i.e., above s q = 24.5 (as previously defined by Schott et al [2003] and Brandt et al [2006]), and 11.7 Sv in the thermocline as follows: 2.5 Sv in the upper thermocline, 8.3 Sv in the lower thermocline layer, and 0.9 Sv in the deep thermocline above 250 m depth (Table 2). Brandt et al [2006] found at 26°W an EUC transport of 3.1 Sv above s q = 24.5 and 10.7 Sv below.…”
Section: Mean Flow At 10°wsupporting
confidence: 58%
See 4 more Smart Citations
“…These results suggest that, while the EUC transport significantly decreases from 35°W to 26°W and loses about 6 Sv, it decreases only modestly farther east, losing 1.7 Sv between 26°W and 10°W. From the 12.1 Sv EUC total transport, 0.4 Sv occurs in the surface layer, i.e., above s q = 24.5 (as previously defined by Schott et al [2003] and Brandt et al [2006]), and 11.7 Sv in the thermocline as follows: 2.5 Sv in the upper thermocline, 8.3 Sv in the lower thermocline layer, and 0.9 Sv in the deep thermocline above 250 m depth (Table 2). Brandt et al [2006] found at 26°W an EUC transport of 3.1 Sv above s q = 24.5 and 10.7 Sv below.…”
Section: Mean Flow At 10°wsupporting
confidence: 58%
“…[2003] at 35°W, and to the 20.0 Sv and 13.8 Sv obtained at 35°W and around 26°W, respectively, by Brandt et al [2006]. These results suggest that, while the EUC transport significantly decreases from 35°W to 26°W and loses about 6 Sv, it decreases only modestly farther east, losing 1.7 Sv between 26°W and 10°W.…”
Section: Mean Flow At 10°wmentioning
confidence: 67%
See 3 more Smart Citations